5-minute Minnie tales - Disney Storybook Artists (California Disney Press, Glendale, 2014)
Minnie Mouse stars in this collection of 12 tales, each of which can be read aloud in about five minutes
English stories
Keywords: Children's stories, American; Disney characters Fiction; Short stories